Recurrence of Pterygium with Conjunctival Autograft Versus Mitomycin C - , Siddiqa Gul, Ashok Kumar Narsani,Shafi Muhammad Jatoi , Mahtab Alam Khanzada, Syed Asher Dabir (Pakistan Journal of Ophthalmology, 2008)
Purpose: To compare the recurrence rate of conjunctival autograft and mitomycin C adjuvant in pterygium excision. Material and Method: This quasi experimental study was conducted in the department of Ophthalmology, Liaquat University of Medical & Health Sciences Jamshoro / Hyderabad, from November 2004 to April 2006. One hundred twelve eyes of 105 patients with primary and recurrent pterygium were treated with conjunctival autograft and mitomycin C 0.02% intraoperatively for 5 minutes, under the topical anesthesia. Patients were followed postoperatively for a period of 6-12 months to find the recurrence of pterygium and complications. All the surgeries were performed by one surgeon. Result: One hundred twelve eyes were randomized to receive conjunctival autograft (CAG n=70) and mitomycin C (MMC n = 42). There were 4 recurrences (5.7%) in the CAG group and 8 recurrences (19%) in the MMC group. There was statistically significant difference in the recurrence rate between the two groups. The post operative complications in MMC were two punctuate epithelial keratitis, two conjunctival cysts, one conjunctival granuloma and one dellen. No significant complication was encountered in conjunctival autograft group. Conclusion: Simple excision of pterygium followed by conjunctival autograft has the lowest recurrence rate and minimal incidence of complications as compared to intraoperative use of mitomycin C.